2018
DOI: 10.1136/bmjoq-2017-000249
|View full text |Cite
|
Sign up to set email alerts
|

E-referrals: improving the routine interspecialty inpatient referral system

Abstract: Interspecialty referrals are an essential part of most inpatient stays. With over 130 referrals occurring per week at the Royal Devon and Exeter Hospital, the process must be efficient and safe. The current paper-based ’white card' system was felt to be inefficient, and a Trust incident highlighted patient safety concerns. Questionnaires reinforced the need for improvement, with concerns such as a lack of referral traceability and delays in the referral delivery due to workload. The aims of the project were to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 1 publication
2
14
1
Order By: Relevance
“…Statistical power may have been lacking for clinical outcomes but the limitations of post hoc power calculations are well documented 18. The improvement in staff experience is similar to that observed in the study by Shephard et al 13…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Statistical power may have been lacking for clinical outcomes but the limitations of post hoc power calculations are well documented 18. The improvement in staff experience is similar to that observed in the study by Shephard et al 13…”
Section: Resultssupporting
confidence: 89%
“…Inpatient e-referrals are growing in use but the evidence base is limited to a handful of studies, mostly designed to assist resource allocation for busy departments 10–12. A recent quality improvement study comparing inpatient e-referrals with paper-based referrals showed improved staff-reported patient safety, user experience and statistically significant reductions in referral time (time from decision to refer to referral submission) and review time (time from referral submission to review) 13…”
Section: Introductionmentioning
confidence: 99%
“…According to the obtained evidence, implementation of the electronic referral system,[ 10 11 12 ] the relationship between health centers and hospitals,[ 2 ] gatekeeping management of Referral system,[ 13 ] and patient-centered communication[ 14 ] are among the factors that result in increasing the efficiency of the referral system. Factors that increase the efficacy of the referral system include the implementation of the electronic referral system,[ 15 ] the use of standard templates for referral letters,[ 16 ] and increasing access through communication and transportation systems. [ 17 ] Also, the factors that ended up with increasing the quality of referral system services are the implementation of electronic referral system,[ 12 18 ] coordination among the three levels of referral system,[ 19 ] continuing education of general practitioners,[ 20 ] increasing access through communication and transportation systems,[ 17 ] and possible modification of referral instructions.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic healthcare information systems worldwide offers many benefits to all healthcare providers concerned with patient management, including real-time queries for medical and personal information, and therefore easier feedback and follow-up. They also reduce the meantime for referral decision and reception of feedback (12,20,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%